Using Anagram Technique to Develop Students’ Vocabulary Mastery to the Seventh Grade Students - Indrawati Indrawati; Febya Resti (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
Abstract The research problems of this study were (1) to find out the application of anagram technique in improving student’s vocabulary mastery and (2) to know whether there was a significant difference in vocabulary mastery between the experimental group where the anagram technique was implemented and the control group which no treatment was given during the experiment. In this study, the writer used the quantitative method with quasi experimental group design. The samples of this study consisted of 36 students of VII E as Experimental Group and 36 students of VII F as Control Group taken from the second year students of seven classes of MTs N Pangkalpinang. The result of the test was analyzed by using statistical analysis of Paired sample t-test and Independent sample t-test. Based on the result analysis, there were two major findings, namely (1) the implementation of Anagram technique in developing students’ vocabulary mastery was successful and the result of difference analysis in post-test of experimental and control group showed that the value of t-obtained was 3.488 which was higher than t-table 2.03 (at the significant level p<0.05 in two tailed testing with degree of freedom 70). The result of this study showed when the means of the post tests between the two classes were compared, the post-test scores were better than the pre-test scores (43.31)for the experimental group (80.89).